Analisis Animo, Motivasi, dan Kesiapan Belajar Mahasiswa Baru Program Studi Teknologi Laboratorium Medik pada Masa Transisi Sekolah ke Perguruan Tinggi di Universitas Muhammadiyah Gorontalo - Muh. Arfah Syam (Transbahasa, 2026)
The transition from secondary school to higher education represents a critical phase that requires academic, psychological, and social adaptation, particularly in laboratory-based programs such as Medical Laboratory Technology (MLT). First-year students encounter significant changes in learning systems, increased demands for independence, and laboratory practices that emphasize precision and professional responsibility. This study aims to analyze the learning enthusiasm, motivation, and learning readiness of first-year MLT students during their transition to university. A qualitative approach with a phenomenological strategy was employed to explore students’ lived experiences through in-depth interviews, observations, and documentation. The findings reveal that students’ experiences are characterized by initial shock toward the university learning system, laboratory practice as both a trigger of enthusiasm and a source of pressure, fluctuating motivation influenced by perceived self-competence, the central role of self-regulated learning in readiness, and social support as a buffering factor in adaptation. Laboratory sessions emerged as a key space for shaping academic and professional identity, while time management and collaborative learning strategies were crucial in sustaining engagement. These findings contribute to a deeper conceptual understanding of first-year transition dynamics in health education and provide practical implications for strengthening academic mentoring systems and fostering self-regulated learning skills among new university students.